The potency of green algae Chaetomorpha crassa Agardh as antioxidant agent from the coastal of Lhok Bubon, West Aceh. (May 2019) - Gazali, M; Zamani, N P; Nurjanah,
Abstract: The coastal of Lhok Bubon at West Aceh district, Aceh Province is ideal habitat for macro algae, such as Chaetomorpha crassa. The objectives of this paper is to analyse the antioxidant activity of C. crassa; to determine their antioxidant activities correlation with total phenolic contents with different extract of marine macroalgae. The C. crassa samples were collected from the coastal area of Lhok Bubon, West Aceh District (latitude 4011'51.07"N; longitude 9601'42.33"E) Aceh Province, Indonesia in June 2017. Several assay by laboratory approach including chemical composition, extraction, phytochemical screening, DPPH, CUPRAC, FRAP assays and measurement of total phenolic content (TPC) was used. The result showed that the antioxidant activities of three extract of green algae C.crassa clearly indicated that they possess antioxidant activity in different method including DPPH, CUPRAC and FRAP. The correlation has indicated to correlate positively between the total phenol content and antioxidant activity with three methods of antioxidant activity.